Promotion mix practices of market leaders: A cross-sector analysis - R. Abratt; N. Chorn; B. I.C. Van Der Westhuizen (South African Journal of Business Management, 1986)
Models which describe promotions practice in various situations have tended to be widely accepted without much attempt at empirical validation. Many approaches rely on the popular dichotomy which separates 'consumer' and 'industrial' marketing. It is argued that this separation is not entirely justified as far as the promotional activities of advertising and selling are concerned, and that the traditional models do not adequately describe promotions strategy in South African companies. The objective of this article is to review some of these approaches and to compare them with current findings of leading South African companies. A study of 25 leading companies across five sectors was undertaken. The purpose was to evaluate their promotions mix practices, and specifically to compare levels of expenditure on advertising and personal selling. The results are somewhat surprising, showing that personal selling expenditure is greater than advertising in all five the sectors studied.
Keywords: 650